1987
DOI: 10.1111/j.1600-0536.1987.tb01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to the active ingredients of Kathon® CG

Abstract: The preservative Kathon CG is a commercial preparation, consisting of 2 active ingredients and other components. 28 patients with contact allergy to Kathon CG participated in a study in which patch testing was performed with serial dilutions, and with 5 chromatographically separated fractions. All reacted to fraction IV, and 2 patients also to fraction II. Mass spectrometry and nuclear magnetic resonance spectrometry identified fraction II and IV to be the active ingredients; 2-methyl-4-isothiazolin-3-one and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
6

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 8 publications
1
87
0
6
Order By: Relevance
“…Wykazano, że Kathon CG ma zależną od dawki zdolność do indukcji i wywołania AKZS u tych zwierząt (17). Na podstawie odrębnej oceny MCI i MI, jako zwią-zek o silnych właściwościach uczulających został sklasyfikowany MCI i to jemu przypisano odpowiedzialność za reakcje alergiczne na MCI/MI (18). W badaniach metodą LLNA (local lymph node assay -badanie lokalnych węzłów chłonnych) u myszy na podstawie oceny wartości EC3 (stężenie związku wywołują-ce 3-krotny wzrost aktywności proliferacyjnej komó-rek węzłów) potwierdzono wysoki potencjał uczulający MCI/MI (9,19) oraz wykazano jego zależność od podłoża (20).…”
Section: Właściwości Uczulające MCI I Miunclassified
See 3 more Smart Citations
“…Wykazano, że Kathon CG ma zależną od dawki zdolność do indukcji i wywołania AKZS u tych zwierząt (17). Na podstawie odrębnej oceny MCI i MI, jako zwią-zek o silnych właściwościach uczulających został sklasyfikowany MCI i to jemu przypisano odpowiedzialność za reakcje alergiczne na MCI/MI (18). W badaniach metodą LLNA (local lymph node assay -badanie lokalnych węzłów chłonnych) u myszy na podstawie oceny wartości EC3 (stężenie związku wywołują-ce 3-krotny wzrost aktywności proliferacyjnej komó-rek węzłów) potwierdzono wysoki potencjał uczulający MCI/MI (9,19) oraz wykazano jego zależność od podłoża (20).…”
Section: Właściwości Uczulające MCI I Miunclassified
“…Na podstawie badań świnek morskich z zastosowaniem metody Magnussona-Kligmana MI uznano za związek o słabym potencjale alergizującym (18). Według innych badań u zwierząt i ludzi (z udziałem zdrowych ochotników), u których MI wielokrotnie aplikowano pod okluzją (human repeated insult patch test -HRIPT), związek wykazywał właściwości uczulające tylko w bardzo wysokim stężeniu (> 600-1000 ppm) (3,21).…”
Section: Właściwości Uczulające MCI I Miunclassified
See 2 more Smart Citations
“…67 Since then, evaluation of MI in the LLNA demonstrated it was sensitizing and confirmed that its potency was in the higher category for classification and labelling (an EC3 value of <2.0%). 27,68,69 In the last 10 years, use of MI alone as preservative has become much more common. In cosmetics, use was restricted to a maximum of 100 ppm in all product categories, but this opinion has been revised recently.…”
Section: An Illustrative Example -Mimentioning
confidence: 99%